2014
DOI: 10.1080/10286020.2014.910197
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic constituents from the roots of Phyllodium pulchellum

Abstract: Three new phenolic constituents 1-3 were obtained from the 95% ethanol extract of the roots of Phyllodium pulchellum (Leguminosae). Their structures were elucidated on the basis of spectroscopic analyses, such as NMR, UV, IR, HR-ESI-MS, and CD. Furthermore, in an in vitro bioassay, all compounds were tested for inhibitory effects against the proliferation of acetaldehyde-stimulated HSC-T6 cells, and compound 3 exhibited potent inhibitory activity with the IC50 value of 7.6 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…3 Other phenolcontaining natural products arise from the direct oxidative coupling of tethered free phenols to afford a phenol-dienone motif (Figure 1B,C). 4,5 Since the discovery that direct phenol oxidation plays a critical role in the biosynthesis of such compounds, 6−8 analogous reagent-based approaches have been of considerable interest for their potential application in the synthesis of plant metabolites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Other phenolcontaining natural products arise from the direct oxidative coupling of tethered free phenols to afford a phenol-dienone motif (Figure 1B,C). 4,5 Since the discovery that direct phenol oxidation plays a critical role in the biosynthesis of such compounds, 6−8 analogous reagent-based approaches have been of considerable interest for their potential application in the synthesis of plant metabolites.…”
mentioning
confidence: 99%
“…Bisphenols constitute an important class of molecules with utility as both complex molecule precursors and biologically active natural products. , Such biologically active compounds often incorporate the bisphenol biaryl motif as part of a polycyclic system (Figure A) . Other phenol-containing natural products arise from the direct oxidative coupling of tethered free phenols to afford a phenol-dienone motif (Figure B,C). , Since the discovery that direct phenol oxidation plays a critical role in the biosynthesis of such compounds, analogous reagent-based approaches have been of considerable interest for their potential application in the synthesis of plant metabolites.…”
mentioning
confidence: 99%
“…The known compounds ( Figure 1) were identified as isoswertisin ( 4 ), [14] taxifolin ( 5 ), [15] caudatan B ( 6 ), [16] (2 R ,4 R )‐2‐(5‐hydroxy‐2‐methylphenyl)‐8‐(3‐methylbut‐2‐en‐1‐yl)‐4‐(l‐oxidaneyl)chromane‐3,7‐diol ( 7 ), [17] 8‐prenykaempferol ( 8 ), [18] 2‐(2,4‐dihydroxyphenyl)‐3,5‐dihydroxy‐7‐methoxy‐8‐(3‐methylbut‐2‐en‐1‐yl)chroman‐4‐one ( 9 ), [19] 8‐prenylquercretin ( 10 ), [20] citrusinol ( 11 ), [21] pulcheloid B ( 12 ), [22] yokovanol ( 13 ), [23] apigenin ( 14 ), [24] 8‐dimethylallyltaxifolin ( 15 ), [25] genistein ( 16 ), [26] naringenin ( 17 ), [27] shuterin ( 18 ), [28] kaempferol ( 19 ), [29] aromadendrin ( 20 ), [30] luteolin ( 21 ), [31] quercetin ( 22 ) [29] by comparing their spectrascopic data with those from previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research had shown that chemical constituents of P. pulchellum included alkaloids, alcohols, and phenols. In total alkaloids part, indolealkylamine (IAA) and β -carboline type alkaloids were its main constituents [ 3 5 ]. To the best of our knowledge, these alkaloids are regarded as the promising plant-derived compounds to treat CNS illnesses, due to their unique complex nitrogen-containing structures to interact with diverse neuronal and molecular targets [ 6 ].…”
Section: Introductionmentioning
confidence: 99%